2020
DOI: 10.17221/26/2019-rae
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of wheat and barley straw

Abstract: Pyrolysing agricultural crop residues and other biomass constitutes a newer method of transforming often difficult, waste materials into a novel type of soil amendment/additive. Simultaneously, this process also makes it possible to exploit part of the energy released in the agricultural production. Biochar, viewed as the solid product of biomass pyrolysis, is a remarkable, porous material, rich in carbon. Two agricultural crop residues, such as wheat and barley straw, were selected for the experimental studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In contrast, Park et al (2014) studied the slow pyrolysis of rice straw and reported that an increase in the temperature of the process from 300 to 700°C resulted in a decrease in the calorific value of the material from 16.6 to 13.6 MJ kg -1 (Park et al, 2014). On the other hand, in a study conducted by Sedmihradská et al (2020), biochar from barley straw prepared at 500°C was characterized by a calorific value at the level of 25.5 MJ kg -1 (Sedmihradská et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Park et al (2014) studied the slow pyrolysis of rice straw and reported that an increase in the temperature of the process from 300 to 700°C resulted in a decrease in the calorific value of the material from 16.6 to 13.6 MJ kg -1 (Park et al, 2014). On the other hand, in a study conducted by Sedmihradská et al (2020), biochar from barley straw prepared at 500°C was characterized by a calorific value at the level of 25.5 MJ kg -1 (Sedmihradská et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the European Biochar Certificate standard (EBC) states that the biochar should have the surface area larger than 150 m 2 g −1 . 65 Therefore, chrysanthemum waste from the beverage industrial is a suitable feedstock for biochar production.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum operating temperature of the application equipment (400 • C) is assumed as the pyrolysis temperature for the system. Based on Sedmihradská's experimental research [47], this pyrolysis process produces a biochar yield of 32.9%, bio-oil yield of 49.9%, and syngas yield of 15.6%. The calorific value of bio-oil and syngas is calculated by the thermochemical characteristics [47].…”
Section: Life Cycle Assessmentmentioning
confidence: 99%